Tuberculoma of the Brain: 3 Case Reports - Islam, Kazi Ashraful; Rahman, Md Mizanur; Akhter, Shaheen; Alam, Syeda Tabassume; Asaduzzaman, Khondoker; Islam, Md Ridwanul (Journal of Chittagong Medical College Teachers' Association, 2011)
Key words: Tuberculoma; children; case report DOI: 10.3329/jcmcta.v21i2.7737 Journal of Chittagong Medical College Teachers' Association 2010: 21(2):41-43